2022
DOI: 10.1007/s00018-022-04540-7
|View full text |Cite
|
Sign up to set email alerts
|

The rs1001179 SNP and CpG methylation regulate catalase expression in chronic lymphocytic leukemia

Abstract: Chronic lymphocytic leukemia (CLL) is an incurable disease characterized by an extremely variable clinical course. We have recently shown that high catalase ( CAT ) expression identifies patients with an aggressive clinical course. Elucidating mechanisms regulating CAT expression in CLL is preeminent to understand disease mechanisms and develop strategies for improving its clinical management. In this study, we investigated the role of the CAT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“… 58 CAT gene promoter contains several CpG islands and previous reports have implicated DNA methylation as a regulatory mechanism of CAT gene expression. 58 , 59 , 60 We found lower promoter methylation level of CAT gene in HPV(+) than HPV(−) OPSCC patients, indicating increased expression of catalase and elevated antioxidant activity, likely acting as a host defense mechanism against exogeneous HPV infection and tumor progression.…”
Section: Discussionmentioning
confidence: 72%
“… 58 CAT gene promoter contains several CpG islands and previous reports have implicated DNA methylation as a regulatory mechanism of CAT gene expression. 58 , 59 , 60 We found lower promoter methylation level of CAT gene in HPV(+) than HPV(−) OPSCC patients, indicating increased expression of catalase and elevated antioxidant activity, likely acting as a host defense mechanism against exogeneous HPV infection and tumor progression.…”
Section: Discussionmentioning
confidence: 72%
“…Some research reported that allele A of rs1001179 (CAT) was associated with a 0.6fold decrease in risk for acoustic neuroma [42]. Galasso et al [43] revealed the importance of the CAT rs1001179 polymorphism with respect to the CAT gene activity. In their model of investigation, leukemic cells harbouring the rs1001179 SNP T allele exhibited a significantly higher CAT expression than the cells bearing the CC genotype, due to the increased binding of two transcription factors, ETS proto-oncogene 1 (ETS-1) and glucocorticoid receptor beta (GR-β).…”
Section: Discussionmentioning
confidence: 99%
“…Some research reported that allele A of rs1001179 ( CAT ) was associated with a 0.6-fold decrease in risk for acoustic neuroma [ 42 ]. Galasso et al [ 43 ] revealed the importance of the CAT rs1001179 polymorphism with respect to the CAT gene activity. In their model of investigation, leukemic cells harbouring the rs1001179 SNP T allele exhibited a significantly higher CAT expression than the cells bearing the CC genotype, due to the increased binding of two transcription factors, ETS proto-oncogene 1 (ETS-1) and glucocorticoid receptor beta (GR-β).…”
Section: Discussionmentioning
confidence: 99%
“…In their model of investigation, leukemic cells harbouring the rs1001179 SNP T allele exhibited a significantly higher CAT expression than the cells bearing the CC genotype, due to the increased binding of two transcription factors, ETS proto-oncogene 1 (ETS-1) and glucocorticoid receptor beta (GR-β). The strength of binding and transcriptional activity of CAT was also dependent on the level of DNA methylation [ 43 ]. These data imply that even though minor alleles are more likely to be risk alleles in complex diseases, this may not always be the case [ 44 ].…”
Section: Discussionmentioning
confidence: 99%